Pengaruh Kebijakan Dividen terhadap Nilai Perusahaan dengan Kebijakan Hutang sebagai Variabel Moderasi - Santi Dharmastri Laksmi, Ida Ayu; Budiartha, I Ketut (E-Jurnal Akuntansi, 2020)
Firm value is defined as market value because firm value is able to provide prosperity for shareholders if the company's share price increases. The purpose of this study is to obtain empirical evidence of dividend policy on firm value and moderation of debt policy on dividend policy on firm value. The study used companies listed on the IDX for the 2016-2018 period with a sample of 37 samples. The analysis technique used is multiple linear regression analysis. Based on the research results, it is known that dividend policy has a negative effect on firm value, debt policy moderates the positive effect of dividend policy on firm value. Dividend policy has succeeded in improving company management. Debt policy can moderate dividend policy, because at the time of distributing dividends the dividend decision is determined by the amount of debt. Keywords: Company Value; Dividend Policy; Debt Policy.